1991
DOI: 10.1016/0168-1702(91)90032-q
|View full text |Cite
|
Sign up to set email alerts
|

The cloning and sequencing of the virion protein genes from a British isolate of porcine respiratory coronavirus: comparison with transmissible gastroenteritis virus genes

Abstract: Previous analysis of porcine respiratory coronavirus (PRCV) mRNA species showed that mRNAs 2 and 3 were smaller than the corresponding transmissible gastroenteritis virus (TGEV) mRNA species (Page et al. (1991) J. Gen. Virol. 72, 579-587). Sequence analysis showed that mRNA 3 was smaller due to the presence of a new putative RNA-leader binding site upstream of the PRCV ORF-3 gene. However, this observation did not explain the deletion observed in PRCV mRNA 2. Polymerase chain reaction (PCR) was used to generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…More than 10 coronavirus N genes have now been sequenced, including those of HCV 229E, TGEV, PRCV, FIPV, CCV, murine hepatitis virus (MHV), HCV OC43, bovine coronavirus (BCV) and infectious bronchitis virus (IBV) (Schreiber et al, 1989;Kapke & Brian, 1986;Britton et al, 1991 ;Vennema et al, 1991 ;Horsburgh et al, 1992;Parker & Masters, 1990;Kamahora et al, 1989;Lapps et al, 1987;Boursnell et al, 1985). Many of these viruses have been sequenced by more than one group; the references quoted here were those used in the sequence analyses shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 10 coronavirus N genes have now been sequenced, including those of HCV 229E, TGEV, PRCV, FIPV, CCV, murine hepatitis virus (MHV), HCV OC43, bovine coronavirus (BCV) and infectious bronchitis virus (IBV) (Schreiber et al, 1989;Kapke & Brian, 1986;Britton et al, 1991 ;Vennema et al, 1991 ;Horsburgh et al, 1992;Parker & Masters, 1990;Kamahora et al, 1989;Lapps et al, 1987;Boursnell et al, 1985). Many of these viruses have been sequenced by more than one group; the references quoted here were those used in the sequence analyses shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Bridgen and others At present the only reported examples of PCR amplification of coronaviral cDNA of unknown sequence have involved amplification with primers derived from closely related coronaviruses. For example, porcine respiratory coronavirus (PRCV), the sequence of which shows a 96 to 98 % amino acid identity to that of TGEV (Britton et al, 1991;Rasschaert et al, 1990), was amplified using TGEV primers (Britton et al, 1991), and feline enteric coronavirus (FECV) was amplified using FIPV primers (Vennema et al, 1992). The approach used in the experiments described in this paper should, however, be applicable to the cloning of any coronaviral genome.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence data revealed that PRCV has a large deletion in the 5' region of the S glycoprotein gene. It has been proposed that the deletion may be related to the differences observed in tissue tropism or pathogenicity between PRCV and TGEV strains [3,30,49]. Researchers have reported that PRCV strains replicate almost exclusively in the respiratory tract [15,48] and usually cause subclinical infections or only mild signs of respiratory disease.…”
mentioning
confidence: 99%
“…Acta Veterinaria Hungarica 62, 2014 terised mainly by deletions in the spike (S) protein (Rasschaert et al, 1990;Britton et al, 1991) emerged. PRCoV is pneumotropic, replicating mainly in alveolar cells, but it can also replicate in the gastrointestinal tract in cells located underneath the villi, and the infections are usually inapparent (Cox et al, 1990).…”
Section: Lőrincz Et Almentioning
confidence: 99%